Definicja dobra i wartości w stoicyzmie: próba reinterpretacji = Definition of Good and Value in Stoicism - Mazur, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Stoics divided philosophy into three parts, physics (which was closer to what we today call ontology), logic (comprising what we today call logic, dialectics, epistemology and philosophy of language) and ethics (comprising elements of philosophical anthropology, traditional ethics, but also the theory of values, i.e. axiology). In my essay, I focus on a part of Stoic ethics, more precisely defined today as axiology. In the face of numerous problems in defining of what the Stoics understand by goodness, virtue and value, and drawing on some modern terminological distinctions, I am looking for a modern reinterpretation of Stoic thinking about values.
Keywords: wartość; dobro; metawartość; stoicyzm; etyka; values; goodness; meta-value; stoicism; ethics